Herman Melville's whaling years - Heflin, Wilson L. (Wilson Lumpkin), 1913- (Vanderbilt University Press, 2004)
"Based on more than a half-century of research, Herman Melville's Whaling Years is an essential work for Melville scholars - and all readers who like adventure. In meticulous and thoroughly documented detail, it examines one of the most stimulating periods in the great author's life - the four years he spent aboard whaling vessels in the Pacific during the early 1840s. Melville would later draw repeatedly on these experiences in his writing, from his first successful novel, Typee, through his masterpiece Moby-Dick, to the poetry he wrote late in life." "During his time in the Pacific, Melville served on three whaling ships, as well as on a U.S. Navy man-of-war. As a deserter from one whaleship, he spent four weeks among the cannibals of Nukahiva in the Marquesas, seeing those islands in a relatively untouched state before they were irrevocably changed by French annexation in 1842. Rebelling against duty on another ship, he was held as a prisoner in a native calaboose in Tahiti. He prowled South American ports while on liberty, hunted giant tortoises in the Galapagos Islands, and explored the islands of Eimeo (Moorea) and Maui. He also saw the Society and Sandwich (Hawaiian) Islands when the Western missionary presence was at its height." "Heffin combed the logbooks of any ship at sea at the time of Melville's voyages and examined nineteenth-century newspaper items, especially the marine intelligence columns, for mention of Melville's vessels. He also studied British consular records pertaining to the mutiny aboard the Australian whaler Lucy Ann, an insurrection in which Melville participated and which inspired his second novel, Omoo."--Jacket